"Behinderung" im Dialog zwischen Recht und Humangenetik - Duttge, Gunnar; Engel, Wolfgang; Zoll, Barbara (Universitätsverlag Göttingen, 2014)
Modern medical technologies, especially the pre-implantation and prenatal diagnosis, have given the possibility of preventive dealing with the risks of physical or mental disabilities. On the other side there is the call for support and "inclusion" of people with disabilities. These opposing trends are critically analyzed and discussed in depth from a legally, genetic, as well as from a medical, social and ethical point of view.